Адаптація технічного обслуговування системи живлення повітрям двигуна основних танків в умовах ресурсних обмежень - Довгопол, Юрій Іванович; Кадиляк, Андрій Теодорович; Степанов, Сергій Сергійович; Мацик, Михайло Васильович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Проведено аналіз наявного парку танків для визначення проблем та загальних технологій обслуговування повітроочисників двигунів. На основі використання статистичного методу, методу основного масиву та дослідження технологій обслуговування повітроочисників мийними засобами технічного призначення, запропоновані основні напрямки їх використання при сервісному обслуговуванні повітроочисників. Створено підґрунтя та надані рекомендації щодо проектування та застосування новітніх технологій для оптимізації сервісного обслуговування двигунів танків.

As a result of the maintenance of armoured artillery armament and equipment in the area of the antiterrorist operation, it was established that the maintenance tasks were solved being limited in forces and means. Personnel conducted the minimum amount of operations, technical maintenance 1 and 2 were not performed in full, level of personnel training is low. In addition, it is noted that the existing maintenance system requires significant improvement. Thus, the imperfect existing maintenance system, failure to meet a certain amount of maintenance work and poor knowledge of operation regulations for the armoured armament material negatively affected, and in some cases, were the main cause of engine failure. Confirmation to this is the data taken from general analysis of the technical state of samples of armoured vehicles and equipment during the practical task accomplishment in the area of antiterrorist operation. Therefore, the reasons for the failure of T-64BV (T-64BM) tanks in 34% of cases were malfunction of the air supply system. In order to prevent the causes of tank engine failure, increase their reliability, it is necessary to outline the prospects of the development of air cleaner stands and the direction of increasing the efficiency of technical maintenance of the air supply system of tank engines. For advanced air cleaner stands, it is advisable to use a modular structure, based on existing stands for use both in stationary and field conditions, using modern industrial materials. The modular structure of a perspective rinse air cleaner should have the following unified components, namely: an electric power supply, a heater, a pump and a bath with a lid. The main directions of increasing the efficiency of operation of engine power supply maintenance by air tanks include the concentration of the research organizations of the Armed Forces of Ukraine on the military-technical direction for conducting systematic research with the aim of improving technical maintenance of the air supply system of tank engines using modern air cleaner stands, scientific-technical support for the purpose of scientific substantiation of ways to improve the system of maintenance of engine air supply system.
Adaptation of technical maintenance of the main tanks engine power supply system in conditions of resources
Keywords: танки; технічне обслуговування; військово-промисловий комплекс; системи живлення двигунів; танкобудування; двигунобудування; танкові арсенали; дизельні двигуни; tanks; detergents; quality; service; air purifier of the engine power system; modern industrial base; optimization